Optimal skill distribution under convex skill costs - Tin Cheuk Leung; Hakki Yazici (Central Bank Review (CBR), 2018)
This paper studies optimal distribution of skills in an optimal income tax framework with convex skill constraints. The problem is cast as a social planning problem where a redistributive planner chooses how to distribute a given amount of aggregate skills across people. We find that optimal skill distribution is either perfectly equal or perfectly unequal, but an interior level of skill inequality is never optimal.
Keywords: 330; Skill distribution; Convex skill costs; Optimal taxation